2022
DOI: 10.48550/arxiv.2204.08837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

4-Dimensional Symmetry Breaking of Light in Kerr Ring Resonators

Abstract: Symmetry breaking of light states is of interest for the understanding of nonlinear optics, photonic circuits, telecom applications and optical pulse generation. Here we demonstrate 4-fold symmetry breaking of the resonances of ring resonators with Kerr nonlinearity. This symmetry breaking naturally occurs in a resonator with bidirectionally propagating light with orthogonal polarization components. The four circulating field components are shown to exhibit multiple and, nested and isolated, spontaneous symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…SSBs in Kerr-resonators have been observed between counter propagating fields [3][4][5][6] and two orthogonal polarization components [7] of light. Recently, the possibility of 4-field SSB in microresonators has been predicted [8]. In this work, we show that 4-field SSBs are also viable in two different arrangements of photonic molecules formed by two identical microresonators having different inter-resonator coupling mechanisms.…”
Section: Introductionmentioning
confidence: 62%
“…SSBs in Kerr-resonators have been observed between counter propagating fields [3][4][5][6] and two orthogonal polarization components [7] of light. Recently, the possibility of 4-field SSB in microresonators has been predicted [8]. In this work, we show that 4-field SSBs are also viable in two different arrangements of photonic molecules formed by two identical microresonators having different inter-resonator coupling mechanisms.…”
Section: Introductionmentioning
confidence: 62%
“…Comparing it with the equations of Cole et al [24,26], we see that the effects of the polarisation components cause not only additional cross-phase modulation terms (and their averages) but also a further additional term, the final term of Eq. ( 1), which is caused by an energy exchange between the two circular components of each beam [22,29]. We note that, if so desired, one may transition Eq.…”
Section: Resultsmentioning
confidence: 99%
“…where E in is the input pump, θ the cavity detuning, η controls the type of dispersion (with its value ±1 referring to normal or anomalous dispersion, respectively), t and τ are both temporal variables but on relative slow and fast time-scales, respectively [28], and A and B control the strengths of self-and cross-phase modulation effects, [11,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSB of light in Kerr resonators has seen a flurry of study and interest in the past half-decade, being predicted and observed for systems with counter-propagating light components [1][2][3], for orthogonally polarized light components [4,5], and also very recently for systems combining both counter-propogating light and orthogonal polarizations components together [6] and containing twinresonator photonic isomers [7].…”
Section: Introductionmentioning
confidence: 99%